The Role of Good Faith: A Case Study on the Application of Good Faith in the CISG - Sedki, Mirco (Department of Commercial Law, 2019)
The work at hand discusses the role of ‘good faith’ in the meaning of Article 7 of the United Nations Convention on Contracts for International Sale of Goods (CISG). The CISG is a sales convention developed by UNCITRAL with the objective to provide a uniform and fair regime for the international sale of goods. As a consequence, the uniform application of the Convention is main concern of the CISG. Art. 7 provides a method to ensure that the Convention is applied in such uniform way. The provision lays down the three principles of interpretation of the CISG: ‘its international character’, ‘uniformity in its application’ and the ‘observance of good faith in international trade’.